2013
DOI: 10.1016/j.devcel.2013.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Control of Hematopoietic Stem Cell Emergence by Antagonistic Functions of Ribosomal Protein Paralogs

Abstract: Summary It remains controversial whether the highly-homologous ribosomal protein (RP) paralogs found in lower eukaryotes have distinct functions and this has not been explored in vertebrates. Here we demonstrate that despite ubiquitous expression, the RP paralogs, Rpl22 and Rpl22-like1 (Rpl22l1) play essential, distinct, and antagonistic roles in hematopoietic development. Knockdown of rpl22 in zebrafish embryos selectively blocks the development of T lineage progenitors after they have seeded the thymus. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 63 publications
4
84
0
1
Order By: Relevance
“…Human RPL10 mutations have been detected in leukemia (64,65) and implicated in abnormal brain development leading to autism (66), intellectual disability (67,68), and microcephaly (69). Moreover, faulty translation resulting from loss of other ribosomal proteins constitutes an important pathogenic mechanism (69,70) and causes diverse developmental defects (71)(72)(73). In addition, dramatically elevated transcription of Scp3l was also observed (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Human RPL10 mutations have been detected in leukemia (64,65) and implicated in abnormal brain development leading to autism (66), intellectual disability (67,68), and microcephaly (69). Moreover, faulty translation resulting from loss of other ribosomal proteins constitutes an important pathogenic mechanism (69,70) and causes diverse developmental defects (71)(72)(73). In addition, dramatically elevated transcription of Scp3l was also observed (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…For example, knockdown of rpl22 in zebrafish embryos results in T-cell developmental arrest, whereas knockdown of the paralogue rpl22l1 blocks the development of hematopoietic stem cells independent of p53 levels. 127 Importantly, in mice, mutations in Rpl38 cause selective effects on axial skeletal patterning and the formation of the mammalian body plan. 128 These tissue-specific phenotypes are mirrored by selective impairment in the translation of Hox genes, key vertebrate developmental regulators.…”
Section: Ribosomal Complexity In Cellular and Developmental Biologymentioning
confidence: 99%
“…Rpl22 morphants exhibited arrested T cell development in a p53-dependent manner, and knockdown of Rpl22l1 impaired the emergence of HSCs in a p53-independent manner. Mechanistically, both Rpl22 and Rpl22l1 bind to smad1 mRNA, which is an important regulator for HSC emergence, but play distinct roles in smad1 expression, with Rpl22l1 facilitating smad1 expression and Rpl22 repressing it [71]. In yeast, mutant analysis showed that cells lacking ribosomal protein paralogs exhibited different phenotypes with distinct gene expression changes and that translation of specific mRNAs required a specific subset of ribosomal proteins [72].…”
Section: Specific Functions Of Ribosomal Proteinsmentioning
confidence: 99%